The Renormalization of Smoking in America: A Conceptual Model of Vaping Behavior - Cano, Cynthia Rodriguez; Totten, Jeffrey W.; Al-Emran, Md (Journal of Marketing Development and Competitiveness, 2020)
Promoted as a safer alternative to burning (traditional, combustible cigarettes) and a means of smoking cessation, heating (chemical aerosols) is a megatrend that has re-normalized smoking in American culture. The purpose of the current study is to develop a conceptual model of vaping. A systematic review of 63 academic articles identified variables and outcomes of vaping. Five antecedents of attitude toward vaping and subsequent intention to vape and use include past behavior, self-concept, sensation seeking, risk assessment, and product awareness. Five variables (e.g., age, gender, education, ethnicity, and attachment style) moderate the positive relationship between intention to vape and vaping. Managerial implications and challenges are proposed: 1) pro-active marketing and agile strategies to account for the inevitable regulatory interventions by the federal government to restrict promotions; 2) price sensitivity of younger consumers commands the monitoring of price strategies to defend market attacks by competitors; 3) vaping may be positioned as brain-altering delivery devices opening markets for chemicals that can be delivered through an aerosols; 4) companies face ethical challenges associated with promoting self-injurious products. Direction for future research (e.g., psychological underpinnings of the model) and limitations of the study are discussed.